New species of Heteropathes (Anthozoa: Antipatharia) expands genus distribution to the NE Atlantic - de Matos, Valentina; Braga-Henriques, Andreia; Santos, Ricardo S.; Ribeiro, Pedro A. (Zootaxa, 2014)
Heteropathes opreski, a new antipatharian species from the northern border of the Oceanographer Fracture Zone is here described and illustrated. An emended diagnosis of the genus and a dichotomous key containing the four Heteropathes species are presented. This species is unique in that it forms smaller colonies compared to the other species in the genus, with some of the lateral pinnules presenting a small ramified subpinnule. Additionally, the polypar spines found on the lateral pinnules are the highest so far recorded in the genus. This record greatly expands the known distribution of this genus, as it was not previously reported to occur in the Northeastern Atlantic.